PENGARUH PREKURSOR DAN ARUS TERHADAP PELAPISAN ZINC OXIDE PADA SERAT KARBON MENGGUNAKAN METODE ELECTROCHEMICAL - Dinata, Fadea; Kristianta, FX; Trifiananto, M; Sidartawan, Robertus; Dwiqoryah, Rika (Jurusan Teknik Mesin, 2024)
Coating is a chemical process that is useful for changing the physical or mechanical properties of the material to be coated. Electrochemical is a coating technology that utilizes chemical processes assisted by electrical energy. The layers that are often grown today are layers that have semiconductor properties. One of the semiconductor layers is ZnO which is often used as a sensor or piezoelectric. This research aims to determine the effect of variations in precursor and current on the results of ZnO coating on carbon fiber used for pulse sensors. The research method was carried out experimentally using a DC Power Supply, USB Oscilloscope and Zinc Acetate Dihydrate precursor solution. The precursor variations in this study were 0.5 gr/50mL and 1.0 gr/50mL, while the current variations were 0.8 A, 1.0 A and 1.2 A. The results showed that the voltage from the pulse sensor was the most high at a precursor of 1.0 gr/50 mL with a current of 1.2 A. It can be concluded that the thickness and structure of the ZnO layer greatly influences the performance of the pulse sensor.